The Relationship Between Optimism, Emotional Factors, and Health Worker Services with Medication Adherence for Pulmonary Tuberculosis Patients at Bades Community Health Center - Ayu Isrotin; Nafolion Nur Rahmat; Sunanto (KHD-Production, 2024)
Pulmonary tuberculosis (TB) is a global health problem characterized by low medication adherence, which can lead to drug resistance and treatment failure. Optimism, emotional factors, and health worker services are believed to play a significant role in adherence among pulmonary TB patients. This study aims to analyze the relationship between optimism, emotional factors, and health worker services with medication adherence for pulmonary TB patients at Bades Community Health Center. This correlational study uses a cross-sectional design and involves 21 pulmonary TB patients in categories 1 and 2 who meet the inclusion criteria. Data were analyzed using linear regression tests to evaluate the relationships between variables. The results show that most respondents have a good level of optimism (66.7%), good emotional factors (61.9%), and receive good healthcare services (81%). Medication adherence among pulmonary TB patients is categorized as adherent in 57.1% of respondents. Bivariate analysis indicates a significant relationship between optimism (p=0.000), emotional factors (p=0.000), and health worker services (p=0.008) with medication adherence for pulmonary TB patients. The multivariate analysis reveals that emotional factors have the strongest influence on adherence, with a beta value of 0.751, indicating that emotional conditions, such as fear, anxiety, or motivation, play a crucial role in influencing patients' adherence to treatment. In contrast, optimism has a lower impact with a beta value of 0.320, while health worker services show a negative association with adherence (beta = -0.254). The emotional factor has been found to have the greatest impact on patient adherence at Puskesmas Bades, while optimism and the quality of healthcare service have a lesser effect. The negative beta value for healthcare service suggests that service quality may need improvement. The focus should be on enhancing emotional support and evaluating service quality to improve patient adherence.